Clinical value of troponin profiles in early post coronary artery bypass grafting acute care in advanced chronic kidney disease patients: An insight into perioperative patient characteristics. (2nd May 2022) - Gobolos, L; Manla, Y; Khan, N; Bhatnagar, G; Aljabery, Y; Sanger, S; Alsindi, F; Hamour, I; Attallah, N; Hogan, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Aims: Diagnosis of type V myocardial infarction (MI) in patients with advanced chronic kidney disease (CKD) undergoing coronary revascularisation surgery (CAB) presents a clinical challenge. We describe postoperative serum troponin (cTn) trends after CAB in CKD stages IV-V, and assess associations with gender, preoperative dialysis, clinical presentation and CAB method. Methods: We analysed 51 patients with CKD stage IV-V who underwent CAB at a single centre between 2016-2021. Data on patient characteristics, CAB surgery, and cTn (T) levels were collected retrospectively, and independently for our Society of Thoracic Surgeons database. Patient characteristics were compared between patients undergoing on-pump vs off-pump CAB using appropriate testing methods. The differences in cTn trends between males vs females, acute coronary syndrome (ACS) vs stable angina, patients undergoing preoperative dialysis vs not, and on-pump vs off-pump CAB at different time points were assessed using repeated measurements, and a p value<0.05 was considered to be statistically significant. Results: Among 51 patients with stage IV (47%) and V (53%) CKD, off-pump CAB was conducted in 41% (21) of the patients, while the rest underwent on-pump CAB. Patients in the off-pump group were older (62.2 vs 56.6 years, p=0.03), and there were no other statistically significant differences in patient characteristics between groups (Table). Over time, cTn levels increased from 0.34 [0.08-0.9] ng/mL at 24h preoperatively to achieve a peak of 0.75 [0.44-1.7] ng/mL at 18h postoperatively. When comparing cTn trends according to gender, preoperative dialysis, clinical presentation and CAB method, cTn levels were higher in males, patients presenting with ACS, patients who did not undergo preoperative dialysis, and in the on-pump CAB group (Figure). However, in this small sample size study, between-group differences in cTn trends did not achieve statistical significance (p=0.26, p=0.18, p=0.5, and p=0.28, respectively). Conclusion: Serum troponin levels peaked consistently by 18h postoperatively in advanced CKD patients undergoing CAB. In addition, males, ACS, on-pump CAB, and non-preoperatively dialysed patients had higher levels of cTn. Further large scale studies are required to definitively evaluate the diagnostic utility and cTn cut-off in this high-risk population.